PEMANFAATAN KACANG TUNGGAK (Vigna unguiculata) DITAMBAH AIR SIWALAN (Borassus flabellifer) SEBAGAI BAHAN BAKU PEMBUATAN KECAP - Siti Miftahul; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2016)
This study aims to prove that cowpea can be used as raw material for the manufacture of soy sauce. Materials used are 200 g / L cowpea without water siwalan and 250, 300, 350, 400, 450 g of cowpea with palm 300 ml of water and added water up to a volume of 1 liter with the same fermentation time is 1.5 months , This research was conducted by completely randomized design, test protein and reducing sugar levels were tested using one-way ANOVA, followed by Least Significant Difference Test at test level 0:05. Organolpeptik test uses 8 semi-trained panelists, the data obtained are transformed to log + ½ further tested using one-way ANOVA and Least Significant Difference test continued at test level 0:05. Results of this study indicate that the use of various concentrations of cowpea no significant effect (P> 0.05) on the soy protein content. The use of cowpea 250 g / L plus water siwalan significant effect on reducing sugar. Flavor of soy sauce made from 200 g / L of cowpea with no added water palm and 250-400 g / L cowpea plus water siwalan panelists disliked. The color of soy sauce made from 200 g / L of cowpea with no added water palm and 250-400 g / L cowpea plus water siwalan preferred by the panelists. The aroma of soy sauce made from cowpea 200 g / L is preferable to the aroma of soy sauce made of 250-400 g / L cowpea plus water palm. Keywords: soy sauce, cowpea, siwalan water, protein, sugar reduction